Increasing positive rate of IgG against hepatitis E virus with steady IgM positivity and clinical incidence: A retrospective seroprevalence time series analysis of HEV from 2012 to 2021 in Chongqing, China - Shi, Lingfeng; Wang, Yanping; Cao, Xuemei; Huang, Wenxiang; Zhang, Shujun (Journal of medical virology, 2023)
China is an epidemic area of hepatitis E, and the serum prevalence data is very important for formulating prevention and control strategies. However, almost all related research in the past decade are cross‐sectional studies. In this study, we analyzed the serological data from 2012 to 2021 in Chongqing for 10 consecutive years. We found that the positive rate of hepatitis E IgG antibody increased gradually, from 1.61% in January 2012 to 50.63% in December 2021. The autoregressive integrated moving average model was used to predict the trend, and it was found that it will continue to show an upward trend in the recent future. In contrast, the positive rate of IgM and clinical incidence of hepatitis E showed a relatively stable trend. Although the positive rate of antibodies gradually increased with age, there was no significant difference in the age distribution of the subjects each year. Therefore, these results suggest that the accumulated infection of hepatitis E in Chongqing may be gradually increasing, but the clinical incidence rate remains unchanged, which provides a new concern for formulating prevention and control strategies.